Understanding Metabolic Regulation Between Host and Pathogens: New Opportunities for the Development of Improved Therapeutic Strategies Against Mycobacterium tuberculosis Infection - Park, Ji-Hae; Shim, Dahee; Kim, Keu Eun San; Lee, Wonsik; Shin, Sung Jae (Frontiers in Cellular and Infection Microbiology, 2021)
Mycobacterium tuberculosis (Mtb) causes chronic granulomatous lung disease in humans. Thus, novel strategies such as host-directed therapeutics and adjunctive therapies that enhance the effect of existing antibiotics have recently emerged to better control Mtb infection. Recent advances in understanding the metabolic interplay between host immune cells and pathogens have provided new insights into how host-pathogen interactions ultimately influence disease outcomes and antibiotic-treatment efficacy. In this review, we describe how metabolic cascades in immune environments and relevant metabolites produced from immune cells during Mtb infection play critical roles in disease progression and the induction of anti-Mtb protective immunity. In addition, we introduce how metabolic alterations in Mtb itself lead to the development of persister cells that are resistant to host immunity and can eventually evade antibiotic attacks. Further understanding of the metabolic link between host and Mtb may contribute to the prevention of Mtb persister cells that are tolerant to the immune environment, but also to enhance host anti-Mtb immunity and the efficacy of existing antibiotics. Overall, this review highlights novel approaches to improve and develop host-mediated therapeutic strategies against Mtb infection by restoring and switching pathogen-favoring metabolic conditions into host-favoring conditions.